Mobiliser l’histoire pour mieux visibiliser les enjeux actuels de la recherche sur le cerveau - Émilie Bovet (Histoire, Médecine et Santé, 2015)
One of the challenges in psychiatric neurosciences is the promotion of the so-called “translational” research, which is the concrete application of research to improve the patient’s condition. It is an important issue because the daily work of caregivers seems far from the promising rhetoric put forward by brain research. If caregivers can try to relieve mental suffering without knowing brain mechanisms, it would be naïve to believe that their practice can avoid the institutional repercussions of psychiatric neurosciences. This paper aims at thinking how an historical analysis of neurosciences can help the future professionals in mental health to be aware of the current institutional transformations in psychiatry and to understand better the influence of brain sciences on these transformations.